VALIDATION TECHNIQUE FOR SIMPLE OPERATIONAL USE (INDRAMAYU, SUMEDANG, AND MAJALENGKA DISTRICTS CASE OF 2003) TEKNIK VALIDASI UNTUK PENGGUNAAN OPERASI SEDERHANA (KASUS KABUPATEN INDRAMAYU, SUMEDANG, DAN MAJALENGKA TAHUN 2003) - Yunus S. Swarinoto (Agromet, 2009)
The model output of rainfall total prediction has to be validated before being applied to the operational use. After understanding the accuracy of this rainfall total prediction output, one has to make decision whether applying it in the field or not. This depends upon the value of accuracy as well. Validation technique for simple operational use can be made by applying Pearson’s correlation coefficient (r), Root Mean Square Error (RMSE), and spatial rainfall defferentiation values (ΔRR). The Wavelet Transformation Technique (WTT) for providing rainfall total prediction output of rainy and transition seasons 2003 had been applied to the domain of interest Indramayu, Sumedang, and Majalengka districts. Results show that during January 2003 (rainy season respectively) r = 0.65 with RMSE = 296 mm and 75.39% spatial disagreement area; but within April 2003 (transition season respectively) r = 0.49 with RMSE = 152 mm and 43.55% spatial disagreement area. Topography condition has play a role to the rainfall deferenciation values, especially for Lee-ward location. This is described by higher differentiation values of rainfall total prediction after reaching the top of elevation above mean sea level.